2018
DOI: 10.1177/1468087418817676
|View full text |Cite
|
Sign up to set email alerts
|

The classification of gasoline/diesel dual-fuel combustion based on the heat release rate shapes and its application in a light-duty single-cylinder engine

Abstract: In this research, there are two major sections for analysis: the characteristics of gasoline and diesel dual-fuel combustion and their application to operating load extension with high thermal efficiency and low emissions. All the experiments were completed using a single-cylinder compression ignition engine with 395 cc displacement. In the first section, the dual-fuel combustion modes were classified into three cases by their heat release rate shapes. Staying at 1500 r/min with a total value of 580 J of low h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In this respect, there have been considerable improvements in engine technologies such as the utilization of renewable fuels, electrification, and development of hybrid engines. Recently, in the context of compression ignition (CI) engines, more advanced combustion strategies such as dual-fuel (DF) combustion have been proposed and used as viable solutions to provide higher efficiency and lower emissions compared to the conventional CI engines [1][2][3][4][5] . The idea of DF combustion in CI engines is to burn one (or a combination of) low reactivity fuel(s) (LRF), such as methane, with the assistance of a high reactivity fuel (HRF), such as diesel.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there have been considerable improvements in engine technologies such as the utilization of renewable fuels, electrification, and development of hybrid engines. Recently, in the context of compression ignition (CI) engines, more advanced combustion strategies such as dual-fuel (DF) combustion have been proposed and used as viable solutions to provide higher efficiency and lower emissions compared to the conventional CI engines [1][2][3][4][5] . The idea of DF combustion in CI engines is to burn one (or a combination of) low reactivity fuel(s) (LRF), such as methane, with the assistance of a high reactivity fuel (HRF), such as diesel.…”
Section: Introductionmentioning
confidence: 99%
“…However, knock intensity, hydrocarbon (HC), CO, and soot morphology were not discussed. Lee et al 4 reported that RCCI mode combustion (70% GSR) depicted 28% longer ignition delay (ID) period, 15% higher thermal efficiency, and 96% lower NOx than that of conventional diesel combustion (CDC) mode. Benajes et al 5 reported the influence of direct injection (DI) of the gasoline/diesel (70:30; 50:50) mixture in RCCI mode combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The paper selection covers all topics of the conference, reflecting current research trends, from the most traditional ones such as injection, sprays and combustion [1][2][3][4][5] to more recent pre-occupations such as studies to improve engine thermal management, [6][7][8] understanding the source of various emissions such as unburned hydrocarbons (UHC) and nanoparticles 9,10 or determining adequate gas exchange strategies for an efficient operation of exhaust after-treatment devices and for emission reduction in cold-start conditions. 11,12 Research on injection and sprays is still a hot topic, for diesel as well as gasoline direct injection (GDI) engines, as it is very relevant to understand the combustion process and the emissions.…”
mentioning
confidence: 99%
“…Improving the thermal efficiency of engines is also one of the important topics that has become very relevant in recent years and is the main concern in three of the selected papers presented here. [6][7][8] Lee et al 6 present another collaborative work between university and industry (Seoul National University and Hyundai Motor Group), this time more focused on the experimental investigation of dual-fuel combustion at various operating loads aimed at improving the gross indicated thermal efficiency of diesel and gasoline engines. Inaba et al 7 also seek to understand how to improve the thermal efficiency and the exhaust emissions of a premixed combustion by controlling the intake oxygen concentration and gas pressure in two geometrically different combustion chambers.…”
mentioning
confidence: 99%
See 1 more Smart Citation